2022
DOI: 10.3390/ijerph19052965
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Patterns of Exclusive and Dual Combustible Tobacco and E-Cigarette Use among US Adolescents—A Nationally Representative Study (2017–2020)

Abstract: This study assessed the sociodemographic predictors of exclusive and dual use of the most frequently used nicotine/tobacco products, e-cigarettes, and combustible tobacco among adolescents. Cross-sectional data was from the 2017–2020 Monitoring the Future nationally representative study of eighth, tenth, and twelfth-grade students. We coded past 30 day nicotine/tobacco use into four mutually exclusive categories: no use, e-cigarette use only, combustible use (cigarette or cigar) only, and dual use (e-cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
(92 reference statements)
2
11
0
Order By: Relevance
“…As children's first teachers and socializing agents, parents' negative health behaviors can act as a bad model for their children (25)(26)(27)(28). In addition, parental socioeconomic status (SES) variables, including educational attainment, income, and occupational status, together with parenting styles, constitute the home environment in which children's behaviors are embedded (25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As children's first teachers and socializing agents, parents' negative health behaviors can act as a bad model for their children (25)(26)(27)(28). In addition, parental socioeconomic status (SES) variables, including educational attainment, income, and occupational status, together with parenting styles, constitute the home environment in which children's behaviors are embedded (25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the intergenerational transmission of risky health behaviors is likely to be in reverse to the SES gradient. However, other research studies showed that with increasing SES, the intergenerational transmission of risky parental health behaviors becomes increasingly apparent (35,37,(53)(54)(55). Yu and Abler (54) proposed that higher education in rural China is often associated with more social activities, and with cigarettes and wine being more accessible.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Some research has examined the overlap between e-cigarette use and dual/polytobacco use among youth in the United States, and the evidence points toward substantial co-use. 7,8,[11][12][13][14][15][16] For instance, in a state-representative study of middle and high school students in Florida, most students who used e-cigarettes reported concurrent use with other tobacco products, with 37.8% reporting dual use (e-cigarettes/other tobacco product), and 40.2% reporting polytobacco use (e-cigarettes/cigarettes/ other tobacco product). 12 Similarly, an analysis using data from the National Youth Tobacco Survey between 2011-2015 found that 52% of students who reported using an e-cigarette during the past month also reported using at least one other tobacco product.…”
mentioning
confidence: 99%
“…8 Epidemiological studies have found differences in the patterns of dual and polytobacco use by sociodemographic group. 11,13,14,16,17 For instance, studies have documented that youth who use three or more tobacco products (i.e., polytobacco use) are more likely to be older 16,18 and male. 3,11,19 Moreover, differences in the patterns of tobacco product use among youth have been observed by race/ethnicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation